2014
DOI: 10.1007/s10911-015-9331-6
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Functions of Milk Proteins: a Comparative Genomics Approach

Abstract: The composition of milk includes factors required to provide appropriate nutrition for the growth of the neonate. However, it is now clear that milk has many functions and comprises bioactive molecules that play a central role in regulating developmental processes in the young while providing a protective function for both the suckled young and the mammary gland during the lactation cycle. Identifying these bioactives and their physiological function in eutherians can be difficult and requires extensive screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 144 publications
0
31
0
Order By: Relevance
“…In contrast, in the majority of eutherian species, lung develops prior to birth, particularly in response to the placenta which regulates intrauterine fetal development by supplying various bioactives (Bell et al, 1999, Garnica and Chan, 1996) supporting fetal respiration (Sibley et al, 1997). Unlike eutherians, the marsupial newborn development relies on factors supplied through milk (Nicholas et al, 1997, Sharp et al, 2014). Based on our previous study (Modepalli et al, 2015), we observed the milk protein collected from different time points of early lactation had temporally related effects on embryonic mouse lung in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the majority of eutherian species, lung develops prior to birth, particularly in response to the placenta which regulates intrauterine fetal development by supplying various bioactives (Bell et al, 1999, Garnica and Chan, 1996) supporting fetal respiration (Sibley et al, 1997). Unlike eutherians, the marsupial newborn development relies on factors supplied through milk (Nicholas et al, 1997, Sharp et al, 2014). Based on our previous study (Modepalli et al, 2015), we observed the milk protein collected from different time points of early lactation had temporally related effects on embryonic mouse lung in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…The gastrointestinal system of postnatal marsupials has been explored, aiding to tell the story of the evolution of this system in vertebrates [96][97][98][99]. Studies on marsupial pouch joeys have shown that every phase of milk has specific factors that trigger phenotypic changes in the neonate stomach [100], and that the milk regulates the microbiota in the neonates' intestine [101].…”
Section: The Main Tissues and Organs In Development In The White-earementioning
confidence: 99%
“…From an evolutionary perspective, its composition has evolved over time in order to provide the infant a well-balanced nutrition and protection against potential infectious pathogens while the neonatal immune system completes its development. 3 Influences on compositional differences include time of lactation, length of gestation, maternal diseases, genotype and diet. 4 The mean protein content gradually decreases from the second to the sixth-seventh month of lactation and stabilizes thereafter.…”
Section: Introductionmentioning
confidence: 99%